Pronunciation Teaching of Young Learners Classroom - Berdiyeva Gulshirin (Zien Journals, 2022)
Recently, interest in foreign languages has increased in Uzbekistan, especially in the English language. This is explained by the role and place of the English language in the modern world: the development of trade and economic relations with English-speaking countries, the emergence of the global computer network Internet, as well as the ability to travel, work and relax abroad. The first acquaintance with the language takes place at the sound, phonetic level, so the formation of pronunciation skills at the initial stage of training is one of the main tasks
Keywords: pronunciation; training; English-speaking; countries